The resilient economic impact of CPEC and future of MNCs: Evidence from Pakistan - Anwar, Syed Umair; Wuyi, Zhang; Ali Shah, Syed Zahid; Ullah, Qudrat; Amir, Syed Muhammad; Syed, Ammara (Frontiers in Environmental Science, 2022)
This article examines the developmental collaboration under CPEC to see if the stated scenario of developed-country progressive cooperation with developing countries holds true on the ground. The economic development of countries is determined by their economic relationships with other countries including megaprojects like CPEC which interlink countries geographically, socially, and economically. The present study has adopted a mixed method technique and the data for this study was gathered using questionnaires and one-on-one interviews with respondents. Furthermore, Pearson correlation, reliability, and KMO were used for analysis. The findings revealed that except for GDP growth and poverty alleviation, all dimensions of resilient economic development such as infrastructure development, investment, economic growth, employment, transportation and knowledge transfer initiatives have positive relationship with CPEC development. Our findings reveal that the GDP and welfare of both Pakistan and China will improve by a maximum of 0.3 percent as a result of transportation innovation. Moreover, the results of the study positively validate the hypothesis. These findings provide policymakers with guidelines for establishing effective policies to support the mega-plan CPEC which will boost global economic growth in the region.